Valproic-induced Fanconi syndrome: Clinical features, risk factors, diagnosis and management - Wang, Chunjiang; Zhou, Yulu; Song, Liying; Deng, Zhenzhen; Fang, Weijin (Frontiers in Medicine, 2022)
Objective: Although Fanconi syndrome (FS) induced by valproate (VPA) has occasionally been reported, the detailed clinical features of the disease remain unclear. The aim of this study was to elucidate the clinical features of patients with VPA-induced FS. Methods: We searched Chinese and English databases for all original studies, clinical reports, and case reports on VPA - induced FS published before March 2022. Results: A total of 29 articles including 54 patients (28 males and 24 females) were included. The patients had a median age of 7 years (range 2, 34 years), had severely disabled (87.0%), tube feeding (64.8%), and received an average of 1.8 medications other than VPA. The median duration of VPA treatment was 4 years (range 0.7, 15.5). Pathological fractures (25.9%), unexplained fever (11.1%), muscle weakness (9.3%), and edema (9.3%) were the most common symptoms, while 18 patients were diagnosed in incidental laboratory tests. Blood tests revealed hypokalemia (69.2%), hypophosphatemia (98.0%), and hypouricemia (93.3%). Urinalysis revealed glucosuria (96.1%), proteinuria (100.0%), generalized hyperaminoaciduria (100.0 %), β2 macroglobulin (100.0%). Decreased percent total reabsorption of phosphate(%TRP) found in 94.1% of patients, and increased fractional excretion of uric acid (FEUA) were found in 100% of patients. The median time to resolution of FS after discontinuation of drug therapy was 3 months (range 0.25, 18). Conclusions: The possibility of FS needs to be considered with long-term VPA administration, especially in young, tube-fed, severely disabled patients who are co-administered with anticonvulsants. Patients receiving VPA should have regular blood and urine tests. Abnormal laboratory values returned to normal levels after VPA discontinuation.